IMPROVING APPROACHES TO THE NORMATIVE MONETARY VALUATION OF RECLAIMED LANDS - Susak, М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
Changes in land reclamation methods at the state level, and the increasing importance of these methods for agricultural businesses, necessitate corresponding adjustments to the information support of rational land use, especially in regards to the evaluation of state land cadastre. The monetary valuation of land plots is vital to the economy and requires improved methods for evaluating reclaimed land. The normative monetary valuation of land plots by the Law of Ukraine “On Land Valuation” dated December 11, 2003, is the capitalized rental income from the land plot, determined according to established and approved standards. Taking into consideration this interpretation, the additional rental income generated by land reclamation should be taken into account in the valuation process. This process is based on the data of the state land cadastre supplemented with information about reclamation networks and components of reclamation networks. Improvement of the methodological approaches to reclaimed lands is carried out based on the integrity of the methodological and informational space in land valuation. Thus, it is proposed to increase the current normative monetary valuation by the coefficient Km for reclaimed lands within the service areas of the land reclamation network. It should be calculated based on the ratio of additional income received due to land reclamation to the total income on reclaimed lands. The authors of the research suggest defining the additional income as the product of additional productivity at the sale price reduced by the amount of additional costs for the operation of the reclamation network and the average rate of agricultural production profit. The proposed approach utilizes normative monetary valuation to objectively assess land plots owned by different business entities. This valuation considers the reclamation conditions and ensures fair redistribution of land rent through the implementation of land tax and lease payment mechanisms.